Determinan Penerapan Basis Akrual Secara Penuh Pada Pemerintah Daerah - Bambang Pamungkas (Jurnal Akuntansi, 2018)
This research meant to obtain a description on how much was the influence of the Indonesian’s Local Governmentsforwardness on the accrual-based Government Accounting System implementation to the quality of Local Government Financial Statements at the early stage of accrual basis executionin 2015. This research develops data from the Indonesian State Audit Institution’s Performance Audit Report on the Local Governments' Efforts in Implementing the Accrual-Based Government Accounting System by using three variables namely the commitment on regulation and policy;the Human Resource Management (HRM) in financial, assets, and Information Technology (IT); and the IT governance. Subsequently, examines the influence of those variables on the quality of 2015 Local Governments' Financial Statements.The results of this study indicate that the human resourceson financial, asset and IT management have a positive influence on the quality of the accrual-based Local Governments' Financial Statements. Conversely, the commitmentto regulation and policies and the IT management did not have a sufficient effect onthe improvement of the accrual-based Local Governments' Financial Statements quality. Thus, this research provides a recommendation for Local Governments, especially for those who have not achieved unqualified opinion, to improve their HRM in financial, asset and IT management in the benefit of escalating theiraccrual-based financial statements quality.